Role of Adipokines and Perivascular Adipose Tissue in Abdominal Aortic Aneurysm: A Systematic Review and Meta-Analysis of Animal and Human Observational Studies - Thanigaimani, Shivshankar; Golledge, Jonathan (Frontiers in Endocrinology, 2021)
Improved understanding of abdominal aortic aneurysms (AAA) pathogenesis is required to identify treatment targets. This systematic review summarized evidence from animal studies and clinical research examining the role of adipokines and perivascular adipose tissue (PVAT) in AAA pathogenesis. Meta-analyses suggested that leptin (Standardized mean difference [SMD]: 0.50 [95% confidence interval (CI): −1.62, 2.61]) and adiponectin (SMD: −3.16 [95% CI: −7.59, 1.28]) upregulation did not significantly affect AAA severity within animal models. There were inconsistent findings and limited studies investigating the effect of resistin-like molecule-beta (RELMβ) and PVAT in animal models of AAA. Clinical studies suggested that circulating leptin (SMD: 0.32 [95% CI: 0.19, 0.45]) and resistin (SMD: 0.63 [95% CI 0.50, 0.76]) concentrations and PVAT to abdominal adipose tissue ratio (SMD: 0.56 [95% CI 0.33, 0.79]) were significantly greater in people diagnosed with AAA compared to controls. Serum adiponectin levels were not associated with AAA diagnosis (SMD: −0.62 [95% CI −1.76, 0.52]). One, eight, and one animal studies and two, two, and four human studies had low, moderate, and high risk-of-bias respectively. These findings suggest that AAA is associated with higher circulating concentrations of leptin and resistin and greater amounts of PVAT than controls but whether this plays a role in aneurysm pathogenesis is unclear.